Concomitancia de mercados competitivos y productividad de la empresa de agua de mesa “Belén”, Ignacio Escudero, Sullana - Piura, 2021 – 2023 - Briceño Ruíz, Anthony (2024)
The phenomenon of multiple competitors entering a market previously dominated by a single business player is an event of considerable economic and strategic relevance. The objective of the research was to evaluate the concomitance of competitive markets on the productivity of the "Belen" company during the period from 2021 to 2023. The design adopted was non-experimental in nature, since the numerical data collected were observed in their original context, covering the number of units generated by the entity, as well as income and expenses derived from commercial activity. The relationship between productivity and the number of competitors in the table water market was analyzed through the application of mathematical models, involving the use of matrices, quadratic functions and linear regression. The modeling results showed an inverse relationship between both variables, indicating that as the number of competitors in the market increased, the company's productivity tended to decrease.